Irish Stereotypes as Seen Through the Irish Lens : The appearance and discussion of stereotypes in Frank McCourt’s Angela’s Ashes - Barclay, Benjamin (My University, 2025)
In my paper I study Frank McCourt’s childhood memoir Angela’s Ashes (1996) from the perspective of two stereotypes commonly connected to Irish people: drunkenness and a propensity for violence. My aim is to analyse these stereotypes from the Irish lens, to see how an Irish author such as McCourt discusses the nature and prevalence of these stereotypes. In my research I use Pramod K. Nayar’s The Post-Colonial Studies Dictionary (2015) as a source for my definition of the term stereotype. I split my research into two main sections: a section for studying drunkenness and a section for the prevalence of violence. Each section I further split into three subsections: one for introducing the stereotype and its historical origins, one for findings of the stereotype in the book, and one for further analysis on what McCourt intends to say about the stereotype. In my conclusion I state that although McCourt does not outright deny the existence of these stereotypical features in the Irish society of his childhood, he provides a detailed description of how and why these features exist. He connects other factors of his childhood like poverty and religion to these stereotypes and does not reduce any character to a mere stereotype. I also add that my research provokes further interest for additional research on the topic of Irish stereotypes through the Irish lens as well as further readings of McCourt’s memoir through the perspective of other Irish stereotypes.
Keywords: stereotypes, Irish, alcohol, violence